Floral Resources Enhance Fecundity, but Not Flight Activity, in a Specialized Aphid Predator, Hippodamia convergens (Coleoptera: Coccinellidae) - Stowe, Hannah E.; Michaud, J. P.; Kim, Tania N. (Frontiers in Ecology and Evolution, 2021)
Adult aphid predators disperse across the landscape seasonally in search of prey aggregations that are patchily distributed and temporally variable. However, flight is energetically costly and consumes resources that could be invested in reproduction. Hippodamia convergens is an important aphid predator in North American cereal crops and other agricultural systems. Consumption of floral resources can enhance adult survival during periods of low prey availability and may improve reproductive success. We tested how an omnivorous adult diet containing floral resources (diluted honey and pulverized bee pollen) interacts with body size to influence reproduction and flight behavior compared to a prey-only diet. Two sizes of beetles were produced by controling larval access to food – 3h daily access produced small beetles; ad libitum access produced large beetles with faster development. Reproductive performance was tracked for 18 days, and female flight activity was assayed via 3h bouts of tethered flight. Diet composition and body size interacted to influence preoviposition period, with large females in prey-only treatments delaying oviposition the longest. The omnivorous adult diet improved 18 d fecundity relative to a prey-only diet, but egg fertility was unaffected. Adult size affected oviposition pattern, with small beetles laying smaller, but more numerous, clutches. Females flew up to 7 km in 6h, but neither body size nor adult diet influenced flight distance, suggesting that all diet treatments generated energy reserves sufficient to power flights of short duration. However, pre-reproductive females flew > 60% further than they did post-reproduction, likely due to the energetic costs of oviposition. Thus, access to pollen and nectar increased reproductive success and altered oviposition patterns in H. convergens, indicating the importance of floral resources in the agricultural landscape to conservation of this predator and its biological control services.